THE INVESTIGATION OF MANUFACTURING OF WORK PIECES WITH THE ROTATION PARABOLOID SHAPE IN THE CNC MILLING MACHINES - Özel, Cihan; Özek, Cebeli (Dokuz Eylül Üniversitesi, 2002)
In this study, it was aimed the manufacturing of work pieces with shape rotation paraboloid which is one of the analytically expressed space shapes in the CNC milling machines. For this purpose, manufacturing equations were obtained and for the calculation of tool paths, it was shown how automatic NC programme was prepared by using macros programme with Fanuc operating system. A work piece was manufactured in the Dyna 2900 Myte CNC milling machine by the prepared programme. In the result of this manufacturing process, paramaters in the manufacturing equations highly affected both surface roughness of work piece manufactured and costs of production

Bu çalışmada, analitik ifadeli uzay şekillerinden biri olan dönel paraboloid şeklindeki parçaların BSD freze tezgahında imalatı amaçlanmıştır. Bu şekilde bir imalat için, dönel paraboloidin imalat denklemleri çıkartılmış ve takım yollarının hesabı için, Fanuc işletim sistemli makro programlama ile otomatik SD programının nasıl hazırlanacağı gösterilmiştir. Hazırlanan bu program ile Dyna 2900 Myte tipi BSD freze tezgahında, bir parça imal edilmiştir. Yapılan bu imalat sonunda, imalat denklemlerindeki parametrelerin hem imal edilen parçaların yüzey pürüzlülüğünü hem de imalat maliyetlerini önemli ölçüde etkilediği görülmüştür
DÖNEL PARABOLOİD ŞEKLİNDEKİ PARÇALARIN BSD FREZE TEZGAHLARINDA İMALATININ ARAŞTIRILMASI